2014
DOI: 10.1115/1.4026941
|View full text |Cite
|
Sign up to set email alerts
|

Self-Lubricating and Wear Resistant Epoxy Composites Incorporated With Microencapsulated Wax

Abstract: Self-lubricating and wear resistant epoxy composites were developed via incorporation of wax-containing microcapsules. The effects of microcapsule size and content and working parameters on the tribological properties of epoxy composites were systematically investigated. The incorporation of microcapsules dramatically decreased the friction and wear of the composites from those of the epoxy. The increased microcapsule content or the incorporation of larger microcapsules decreased the friction and wear of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…When the steel ball is slid on the epoxy under the higher normal load of 5 N, the epoxy exhibits a lower friction coefficient of about 0.56. Nor mally, an adhesion between two contacting surfaces can result in a high friction due to effective interfacial shear strength between them [22], Wear debris generated can reduce the interfacial shear strength between two contacting surfaces by serving as spacers to lessen a direct contact between them and freely rolling or sliding under a lateral force [7][8][9]15,23,24], In addition, surface roughen ing can lessen the interfacial shear strength between two contact ing surfaces by reducing a real contact area between them [7-9,15,23,24], It is therefore understandable that the higher nor mal load of 5 N results in the higher surface wear of the epoxy, which in turn gives rise to the lower friction of the epoxy via the higher surface roughening and the larger quantity of wear debris [7][8][9]15,23,24],…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the steel ball is slid on the epoxy under the higher normal load of 5 N, the epoxy exhibits a lower friction coefficient of about 0.56. Nor mally, an adhesion between two contacting surfaces can result in a high friction due to effective interfacial shear strength between them [22], Wear debris generated can reduce the interfacial shear strength between two contacting surfaces by serving as spacers to lessen a direct contact between them and freely rolling or sliding under a lateral force [7][8][9]15,23,24], In addition, surface roughen ing can lessen the interfacial shear strength between two contact ing surfaces by reducing a real contact area between them [7-9,15,23,24], It is therefore understandable that the higher nor mal load of 5 N results in the higher surface wear of the epoxy, which in turn gives rise to the lower friction of the epoxy via the higher surface roughening and the larger quantity of wear debris [7][8][9]15,23,24],…”
Section: Resultsmentioning
confidence: 99%
“…Materials modified with solid lubricants, such as graphite, molybdenum disulphide, polytetrafluoroethylene, and so on, can exhibit better frictional performance than met als [3,4], External liquid lubricants, such as liquid paraffin, base oil, wax, etc., can improve the tribological properties of polymer composites in most cases [5,6]. In addition, incorporation of microencapsulated wax or microencapsulated mixture of wax and multiwalled carbon nanotubes in polymer matrices formed a new type of polymer composites for relatively low friction and wear applications [7][8][9]. However, prolonged rubbing under any condi tion can easily introduce surface damages to consequently bring a significant failure of tribological components in service.…”
Section: Introductionmentioning
confidence: 99%
“…The wax lubricant, Episol B2538, was encapsulated by poly(ureaformaldehyde) (PUF) shell using the similar procedure as stated in references [7,16,[26][27][28]. Briefly, 30 g wax was charged into a beaker with liquid mixture consisting of 100 ml de-ionized (DI) water, 25 ml of an aqueous solution containing 2.5 wt.% EMA, 2.5 g urea, 0.25 g resorcinol, and 0.25 g NH 4 Cl at 400 rpm by a mechanical stirrer (Caframo, Model: BDC6015).…”
Section: Samplementioning
confidence: 99%
“…They also found that epoxy composites containing microencapsulated mixture of multiwalled carbon nanotubes (MWCNTs) and wax lubricant exhibited the dramatically lower friction and wear than neat epoxy due to the combined lubricating effects of MWCNTs and released wax lubricant [7]. Moreover, Khun et al [16] revealed that the higher wax lubricant filled microcapsule content or incorporation of larger microcapsules resulted in the lower friction and wear of epoxy composites due to the larger amount of released wax lubricant during wear test. However, incorporation of microcapsules significantly reduces the mechanical properties of polymer composites, such as hardness and elastic modulus, as a result of the much lower mechanical strength of microcapsules than that of polymer matrix [7,13,14,16].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation